Speculative Carcinogenicity Assessment of Polycyclic Aromatic Hydrocarbons Found in Some Anti-Diarrheal Herbal Drugs Sold in Ondo State of Nigeria - Akintelu , Sunday Adewale; Folorunso, Aderonke Similoluwa; Folorunso , Femi Adekunle (Iraqi Journal of Science, 2021)
The conviction that herbal drugs have enormous health benefits has led to increase the rate of their consumption by Nigerians. The aim of this study was to assess the carcinogenic property of some popularly consumed anti-diarrheal herbal drugs via polycyclic aromatic hydrocarbons (PAHs) quantification. Three prevalent anti-diarrhea herbal drugs , Odunmo herbal drug (Hibiscus rosa-sinensis and Bacopamonnieri), Orogun herbal mixture (Hibiscus sabdariffaI and Hedera helix), and Alora herbal syrup (Aloe vera and Hibiscus sabdariffaI) were bought for the purpose of this study and they were coded as samples A, B, and C, respectively. The ultrasonic extraction of the herbal drugs was carried out using standard procedures. The crude extracts obtained were purified using a chromatographic method. The concentrations of PAHs were quantified using gas chromatography flame ionization detector (GCFID). The diagnostic indices, group distribution, toxicity equivalence and exposure dosage were estimated. The cancer risk values were theoretically speculated based on concentrations of PAHs in the tested herbal drugs, associated with the published estimates of each concentration to cause cancer and the calculated exposure doses of the anti-diarrhea herbal drug samples were within three age groups (children, Preteen and adult). The highest concentration of total PAHs was observed in sample A (58.2815mg/kg) and the lowest concentration in sample B (44.1898mg/kg), but the concentration of total PAHs in sample C was 47.4169 mg/kg. The highest percentage of carcinogenic PAHs in the anti-diarrheal herbal drugs was found in sample C (48.66%) and the lowest in sample B (38.17%). The diagnostic indices confirmed a pyrogenic source of PAHs. Group distribution of PAHs showed that the herbal drugs are weakly carcinogenic due to high concentrations of low and moderate molecular weight PAHs. The cancer risk estimated for all the age groups where below the limit established by the United State Environmental Protection Agency (USEPA) for cancer (1 x 10-6). This ascertained that the use of these herbal drugs cannot cause cancer. However, consumers of these herbal drugs should take necessary precautions as excessive intake can lead to dangerous health implications.